Presence of genes encoding aminoglycoside-modifying enzyme (AME) and virulence factors in high-level aminoglycoside-resistant (HLAR) Enterococcus strains isolated from retail chicken meat in Turkey - Yalçın, M; Özden Tuncer, B; Akpınar Kankaya, D; Tuncer, Y (Journal of the Hellenic Veterinary Medical Society, 2024)
In this study, the presence of aminoglycoside-modifying enzyme (AME) and virulence factor genes were investigated in previously isolated 32 high-level aminoglycoside-resistant (HLAR) Enterococcus strains isolated from retail chicken meat in Turkey. At least one AME-encoding gene was detected in HLAR enterococci by polymerase chain reaction (PCR). The ant(6ʹ)-Ia was identified as the most prevalent (87.5%, 28/32) AME gene. The aph(3ʹ)-IIIa (78.13%, 25/32), ant(4ʹ)-Ia (68.75%, 22/32), aph(2ʹʹ)-Ib (62.5%, 20/32), aac(6ʹ)-Ie-aph(2ʹʹ)-Ia (21.88%, 7/32) and aph(2ʹʹ)-Ic (9.38%, 3/32) are the other detected AME-encoding genes in strains. The aph(2ʹʹ)-Id was found in none of the HLAR strains. The aph(2ʹʹ)-Ib and ant(6ʹ)-Ia were identified as the most frequently AME-encoding genes in high-level gentamicin-resistant (HLGR) and high-level streptomycin-resistant (HLSR) strains, respectively. Among the 32 HLAR strains, only E. faecalis MSE61.1 and E. avium MSE63.1 were found capable of hydrolyzing gelatine. All HLAR strains showed α-hemolytic activity except E. durans MG13.4 and E. casseliflavus MGM111.1, which were exhibited β- and γ-hemolytic activity, respectively. It was determined that all HLAR strains, except E. durans MGE13.1 and MGE63.1, contain at least one virulence factor gene. The efaAfm (87.5%, 28/32), acm (65.63%, 21/32) and gelE (37.5%, 12/32) were found to be the most prevalent virulence factor genes. HLAR enterococci strains that have the virulence factor genes may pose a risk to consumer health.